Determining critical risk factors affecting public‐private partnership waste‐to‐energy incineration projects in China. Issue 4 (17th December 2019) - Cui, Caiyun; Sun, Chenjunyan; Liu, Yong; Jiang, Xiaoyan; Chen, Qing
Abstract: As the most effective way to manage the surge in municipal solid waste (MSW) and global energy issues, waste‐to‐energy (WTE) incineration plants have been actively promoted by the Chinese government, and the public‐private partnership (PPP) procurement model is widely used to improve management efficiency. However, risk events have occurred frequently in this industry due to a lack of practice experience and to poor risk management. To investigate the potential risk factors in PPP WTE incineration projects in China, this paper aims to identify critical risk factors by assessing their severity and occurrence probability. Opinions of industry experts were collected via an empirical questionnaire survey. The respondents were invited to rate a total of 18 risk factors that impact the success of PPP WTE projects as gleaned from previous research. The overall results ranked risk factors based on risk impact and showed that public opposition, government decision making, defective legal and regulatory systems, environmental pollution, lack of supporting infrastructure, and government credit are the top six risk factors affecting the sustainable development of PPP WTE incineration projects. In addition, the causes and consequences of each critical risk factor are comprehensively analyzed. Lastly, practical and managerial implications are analyzed in terms of their management of these critical risks. The originality of this research lies in thoroughly identifying potential implicit risk factors according to the current social background using an empirical questionnaire survey based on case study findings. The results of this study are expected to improve risk management and facilitate the sustainable development of the PPP WTE incineration industry in China. Abstract : Risk events have occurred frequently in this WTE industry due to lack of practice experience and poor risk management. Based on previous research, six critical risk factors affecting the sustainable development of PPP WTE incineration projects were identified through questionnaire surveys among experts in this industry. Practical and the managerial implications are analyzed regarding their management of these critical risks.